FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA KABUPATEN TANA TORAJA - Rusdi, H Muh; Ayuliani, Ismi (Jurnal Ekonomi Balance, 2015)
The purpose of this study is to analyze the factors that influence the human development index of Tana Torajad Regency within 10 years, starting from 2004-2013. The dependent variable in this study is the human development index (Y), while the independent variable is the percentage of the poor (X1) and economic growth (X2). The method of analysis used in this study is the method of multiple linear regression statistical analysis and analysis tool used to process data that is by using SPSS 16.0. The result of data analysis shows that the percentage of poor people significantly influence the human development index (HDI) of Tana Toraja Regency. From result of regression test, it is known that the value of sig = 0,016 <0,05 because sign value less than 0,05 means there is negative and significant influence with IPM. Similarly with the influence of economic growth (PDRB) on human development index (IPM) Tana Toraja , can be said to have a positive and significant effect. It can be seen from the result of regression test it has sig value = 0,027 <0,05, it means there is positive and significant influence. Thus the hypothesis is proved.